2013
DOI: 10.25267/rev_eureka_ensen_divulg_cienc.2013.v10.iextra.03
|View full text |Cite
|
Sign up to set email alerts
|

Las emociones sobre la enseñanza-aprendizaje de las ciencias y las matemáticas de futuros profesores de Secundaria

Abstract: Las emociones en los estudios de Didáctica de las Ciencias cada vez se tienen más en cuenta, sin embargo son pocos los trabajos dirigidos a los profesores en formación. En este trabajo se analizaron las emociones de 38 futuros profesores de secundaria que cursan el

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 39 publications
0
2
0
2
Order By: Relevance
“…Based on the studies by Dávila et al [35], Oyarzún and Valdés-León [36], Mellado et al [52], Borrego et al [53], and Bravo et al [54], it can be concluded that the study of emotions is a significant trend in recent years in the field of specific didactics.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the studies by Dávila et al [35], Oyarzún and Valdés-León [36], Mellado et al [52], Borrego et al [53], and Bravo et al [54], it can be concluded that the study of emotions is a significant trend in recent years in the field of specific didactics.…”
Section: Discussionmentioning
confidence: 99%
“…Con respecto a las preguntas sobre ventajas y desventajas de la implementación de AE en las clases de ciencias, las menciones relacionadas con las actitudes hacia la ciencia y sobre la ciencia representa un 31%, repartidas entre actitudes como la "motivación y la "participación" Estos resultados son bastante semejantes a los expresados en otros trabajos en los que se encuestó a futuros profesores Fernández-Marchesi y col., 2017). Podría deberse a que las respuestas están vinculadas con los recuerdos y emociones de la propia biografía académica y escolar (Costillo-Borrego, Borrachero Cortés, Brígido Mero, y Mellado, 2013). Esto también indica una visión tradicional, en otras actividades prácticas muchos profesores tradicionalmente se decantan sobre todo por el aspecto positivo de las salidas sobre las actitudes de los alumnos (Bitgood, 1989;Meredith, Fortneer, y Mullins, 1997), sosteniendo que son sobre el campo de las emociones de los alumnos donde las salidas a la naturaleza inciden en mayor medida.…”
Section: Concepciones Sobre Los Objetivos Las Ventajas Y Las Desventajas De Las Aeunclassified
“…The majority of studies in the field of science education report that positive emotions and enjoyment from learning science play a significant role in the learning outcomes and serve as a driving force for self-learning, and retaining knowledge (Alsop & Watts, 2003;Järvenoja & Järvelä, 2010). So, as the processes of learning and teaching science are not merely cognitive but are highly charged with feelings, the importance of emotions in teaching and learning advocates the need to consider the cognitive and affective dimensions, and metacognitive regulation should be expanded to include not only cognitive but also emotional regulation (Costillo, Borrachero, Brígido & Mellado, 2013, Sutton & Wheatley, 2003. In the case of PTs, the emotional aspect is especially critical at this stage due to, on one hand, the first teaching experiences (that occurs during teaching practices) are emotionally very strong and can be traumatic for future teachers, which are especially vulnerable; and on the other hand we cannot ignore that they usually have negative emotions towards science and teaching science (Evagorou et al, 2014;Evagorou & Mauriz, 2017), which is another barrier to overcome.…”
Section: A8 Observe What Happens and Analyze The Data Does It Matchmentioning
confidence: 99%